Pengaruh Penggunaan Pay Later, Gaya hidup, Pendapatan Orang Tua Terhadap Financial Management Behavior pada Mahasiswa Fakultas Ekonomi Universitas Muhammadiyah Sukabumi - Rahayu, Devita; Eriswanto, Elan; Suherman, Acep (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
This research aims to determine the effects of the variable pay later usage, lifestyle, and income of parents on the financial management behaviors of students at the Economics Faculty of Muhammadiyah University Sukabumi. This research is a quantitative study, conducted using primary data in the form of a questionnaire distributed online via google form. The sampling technique use non-probability sampling method with purposive sampling, involving a sample of 81 participants. Data collection was conducted through questionnaires, and the data analysis was carried out using SPSS IBM 26 software. The result of this research is that pay later usage does not significantly influence financial management behavior. In contrast, both lifestyle and income of parents have a positive and significant partial impact on financial management behavior. Furthermore, when considered together, pay later usage, lifestyle, and parental income demonstrate a positive and significant effect on financial management behavior.